Optimization of Stunting Prevention Through Mother Classes for Toddlers 0-5 Years in the Work Area of ​​the Ciherang Health Center, Cianjur Regency: Optimalisasi Pencegahan Stunting Melalui Kelas Ibu Balita 0-5 Tahun di Wilayah Kerja Puskesmas Ciherang Kabupaten Cianjur - Hartati, Sri; Ayu, Shinta Arini; Widianti, Rina Andriana; Fauziah, Syifa; Rahmaniar, Syalsa Adelia (Jurnal Pengabdian Masyarakat Kesehatan Terkini, 2023)
Nutritional problems, especially stunting in toddlers can hinder children's development, with negative impacts that will take place in later life such as intellectual decline, vulnerability to non-communicable diseases, decreased productivity leading to poverty and the risk of giving birth to babies with low birth weight. This community service aims to find out the optimization of stunting prevention through classes for mothers of toddlers 0-5 years in the working area of ​​the Ciherang Health Center, Cianjur Regency. The method used is active lectures and discussions as well as demonstrations in the class of toddler mothers divided by age group 1-12 months, 12-24 months, 24-60 months and conducting pre and post tests. Participants involved were 30 people with details of 10 people each in each class. The results of the service found that the class of mothers of toddlers 0-5 years had a significant influence on increasing mothers' knowledge about stunting prevention.